Fat mimetic capacity of Chlorella vulgaris biomass in oil-in-water food emulsions stabilized by pea protein - Sousa, Isabel (2010)
Vegetable proteins proved to be good emulsifiers for food emulsions with dietetic advantages. The use of these emulsions as car- riers for healthy ingredients, such as colourings, with antioxidant and other beneficial properties, is an interesting subject. In this work, the capacity of the biomass of the microalga Chlorella vulgaris (which has been widely used as a food supplement) as a fat mimetic, and its emulsifier ability, was evaluated. Pea protein emulsions with C. vulgaris addition (both green and orange – carotenogenic) were prepared at different protein and oil contents. The rheological properties of the respective food emulsions were measured in terms of the viscoelastic properties and steady state flow behaviour and texture properties. It was observed that the two microalgal forms evidenced a fat mimetic capacity in these emulsions, the performance of the green stage of this C. vulgaris organism was significantly (p < 0.05) better than the orange stage.